Impending conservation crisis for Southeast Asian amphibians - Rowley, Jodi (The Royal Society, 2010)
With an understudied amphibian fauna, the highest deforestation rate on the planet and high harvesting pressures, Southeast Asian amphibians are facing a conservation crisis. Owing to the overriding threat of habitat loss, the most critical conservation action required is the identification and strict protection of habitat assessed as having high amphibian species diversity and/or representing distinctive regional amphibian faunas. Long-term population monitoring, enhanced survey efforts, collection of basic biological and ecological information, continued taxonomic research and evaluation of the impact of commercial trade for food, medicine and pets are also needed. Strong involvement of regional stakeholders, students and professionals is essential to accomplish these actions.